Analysis of forensic autopsy cases associated with epilepsy: Comparison between sudden unexpected death in epilepsy (SUDEP) and not-SUDEP groups - Zhang, Xian; Zhang, Jianhua; Wang, Jinming; Zou, Donghua; Li, Zhengdong (Frontiers in Neurology, 2022)
Epilepsy is a common and chronic neurological disorder characterized by seizures that increase the risk of mortality. SUDEP is the most common seizure-related category of death. A retrospective study of forensic autopsy cases from 2002 to 2021, performed by the Academy of Forensic Science (Ministry of Justice, China) identified a total of 31 deaths associated with epilepsy. We analyzed these cases to find the differences between individuals who died of SUDEP (SUDEP group) and individuals with epilepsy who died suddenly due to unrelated causes (not-SUDEP group). As a result, 13 of these cases met the general accepted definition of SUDEP; and 18 of the cases were classified as not-SUDEP. The mean age of the not-SUDEP group was significantly higher than that of the SUDEP groups (p<0.05) and there were more cases without a clear cause of epilepsy in the SUDEP group than in the not-SUDEP group (p<0.05). Death position differed significantly between the two groups, with more cases dying in the prone position in the SUDEP group (p<0.05). Complete autopsies were performed in 24 of 31 cases. There were no significant differences between the SUDEP and not-SUDEP groups in terms of the weights of the heart, lungs and brain, or in terms of ventricular thickness (p>0.05). Moreover, the SUDEP group featured a significantly larger number of cases with coronary lesions (grades 1-3) when compared with the not-SUDEP group (p<0.05). Neuropathological lesions were identified in 12 of 13 SUDEP cases (92.3%), cardiac lesions were present in 10 cases (76.9%) and pulmonary edema and pulmonary congestion were present in all cases. The primary cause of death in 13 of the 31 cases was seizure disorder or epilepsy. The primary mechanism of death in SUDEP group was mainly asphyxia while that in the not-SUDEP group was cardiopulmonary failure (p<0.05). Patients in the prone position had a significantly higher risk of asphyxia than those who were not. Here, we investigated the key characteristics between SUDEP and not-SUDEP death cases. Although further studies are needed to distinguish SUDEP from other death cases, our study may help to facilitate forensic diagnosis in presumed SUDEP cases.